Le città invisibili sulle mappe del mondo. Una ricognizione (ENTHYMEMA, 2020)
Invisible Cities by Calvino has been translated into 42 languages and published in 46 countries since 1974 – the year of the first foreign editions. This contribution explores the cases of countries that are more representative of the peculiarities of Invisible Cities’s reception around the World, exploring his international fortune and the way it became part of last century’s literary canon. Among the various elements under consideration there are the chronology of the editions, the publications in specific editorial collections, the role played by publishers and translators and the recognition from the foreign critics.
Keywords: Italo Calvino; Invisible cities; William Weaver; Helen Wolff; Literary Canon; Translation; Publishing; Paratexts.